Ciborgues são elas, aliens são os outros : genre e gender em Ursula Le Guin - Silva, Erica Soares (2022)
The historiography of the science fiction literary genre shows us, at the same time, a dividend of female writers and a silent hiatus of female voices in the production of scientific literature in previous centuries. In this sense, the centrality of this research is to analyze and compare the process of estrangement between the genre and gender facets in the novel The Left Hand of Darkness by Ursula K. Le Guin (1969) from the cyborg myth studied by Donna Haraway (1985). In this follow-up, this research includes feminist and gender studies, theories of countersexuality and queer. Considering the encounter with difference and with the paradoxical constructs of the cyborg and its apogee in 20th century western pop culture, this prerogative includes the androgynous figuration of the British singer David Bowie (1947 - 2016), considered by pop culture as a " star man”. Thus, through the analysis of Ursula Le Guin's novel, representative connections between genre (genre) science fiction and genre (gender) as a binary, historical and sociocultural construction are proposed. The narrative in question offers a proposal of sci-fi narrative transcendence that is built between utopian and dystopian discourses. Thus, we wish to approach dialogues between the (re)organization and (re)construction of the characters, since, deprived of the natural construction of feminine and masculine, they subvert the prevailing imperative parameters. It also seeks to recover issues of female authorship in fictional genres and how the transgression of women writers influence a field of writing considered for a long time a field of production of male authors. In this context, the appreciation of the work that makes up this dissertation denoted the existence of parallel relationships that approach anthropological, socio-political, feminist and cultural themes in their historiographical clippings and the (re)existence of women in science fiction. In order to carry out such correlations, studies proposed by the systematic and methodological aspects of Comparative Literature were used, which they designate as this study of a comparative nature.